Analisis Persepsi, Sikap, dan Perilaku Remaja mengenai Isu Gender dalam Pencegahan Infeksi Menular Seksual - Margiyati (Medico Insight Innovation Initiative, 2025)
Sexually transmitted infections (STIs) remain a significant public health concern, particularly among adolescents who are in a psychosocial developmental stage that increases vulnerability to environmental influences. This study aimed to explore students’ perceptions, attitudes, and behaviors regarding gender in STI prevention efforts at SMA IT Abu Bakar Yogyakarta. A qualitative descriptive–exploratory design was employed. Participants were selected using purposive sampling and consisted of six science-track students aged 16–17 years, including both male and female students. Data were collected through semi-structured in-depth interviews supported by field notes. Qualitative data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that students generally hold egalitarian perceptions of gender, recognizing that both males and females share equal responsibility in preventing STIs. Students’ attitudes toward STI prevention were predominantly positive, characterized by rejection of risky sexual behaviors without stigmatizing individuals affected by STIs. In terms of behavior, students demonstrated self-regulatory practices such as avoiding premarital sexual activity, being selective in social interactions, and strengthening religious values. The study concludes that the integration of Islamic-based education plays an important role in shaping adolescents’ awareness, attitudes, and preventive behaviors related to STI control within a gender-equitable framework.